Toward Standardization of Hair Cortisol Measurement: Results of the First International Interlaboratory Round Robin. Issue 1 (February 2015) - Russell, Evan; Kirschbaum, Clemens; Laudenslager, Mark L.; Stalder, Tobias; de Rijke, Yolanda; van Rossum, Elisabeth F. C.; Van Uum, Stan; Koren, Gideon
Abstract : Background: The importance of hair cortisol as a long-term retrospective measure of systemic cortisol exposure is being increasingly recognized, and over recent years, the field of hair cortisol analysis has seen rapid expansion with laboratories around the globe, integrating hair cortisol analysis into their study designs. These laboratories use different methods of analysis, and presently, no attempt has been made to compare them. To move toward clinical utilization of this novel method, international benchmark reference values must be established. For that end, 4 leading laboratories in hair cortisol testing set up a protocol for comparison of the methods used by them. Methods: Four immunoassay methods and 2 liquid chromatograph–mass spectrometry (LC–MS/MS) methods were compared by analyzing the same hair samples representing the low, intermediate, and high ranges of hair cortisol concentrations (HCC). Results: HCC determined by the 4 immunoassay methods were highly and positively intercorrelated (r 2 between 0.92 and 0.97; all P < 0.0001) in all comparisons of individual laboratories. Additionally, each laboratory's immunoassay HCC had significant positive correlations (r 2 between 0.88 and 0.97; all P < 0.0001) with each of the 2 LC–MS/MS methods, which produced practically identical results. Conclusions: This study indicates that laboratories using immunoassays can use a correction factor that will convert results into standard LC–MS/MS equivalents.